Implementação da abordagem CTSA em uma sequência didática sobre vacinas para o ensino de Biologia - Simone Braga Dias (2022)
In the face of the current scenario of planetary emergency, experienced by the severity of the COVID-19 pandemic, in expectation to control of the disease through vaccination of the entire population, becomes even more evident the importance of scientific, technological, and social training in basic education. The knowledge of the relation between public health and immunization by vaccines tends to assist in this crisis context and protect the future generations. Therefore, we sought to highlight the requirement of new teaching approaches in biology classes, to create a learning environment that encourages participation and exercise of argumentation in problem-solving situations, resulting in citizens' education capable of making assertive decisions regarding their individual life and collectivity. We seek to promote scientific literacy to instrumentalize the students in the cognitive realm, democratizing the scientific knowledge scientific access, enabling them to understand and debate the relations between science, technology, and society in their everyday life. For this purpose, we use the Science-Technology-Society-Environment (STSE) approach in a didactic sequence with three moments, that aims to promote the appropriation of scientific-technological knowledge about vaccines and health, allowing the exchange between knowledge and values of high school students, from a public school in Minas Gerais state. In this process, we propose, based on the use of the Digital Information and Communication Technologies (DTIC), the production of a booklet of digital scientific divulgation. Through scientific literacy and vaccines awareness, we hope to engage the students in remote actions of health education, and sensitize the school and surrounding community about the importance of vaccination to prevent of infectious diseases, such as COVID-19.